Conceptualizing feedback in computer-based L2 language listening. Issue 5 (4th July 2022) - Cárdenas-Claros, Mónica Stella
Abstract: This paper reports the results of three independent qualitative case studies that examined interactions with feedback as L2 listeners worked in self-regulated environments. Data on high-intermediate learners of English were collected from case studies conducted in Australia, Colombia and Chile. Results show that L2 listeners across case studies used feedback to assess performance, to ease task completion, and to regulate listening comprehension processes. We discuss reasons along with integrated data and propose a three-level preliminary framework for conceptualizing feedback in computer-based L2 listening.